2022
DOI: 10.1016/j.gerinurse.2022.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on older adults: Results from an annual survey

Abstract: Objectives Assess well-being among older adults through secondary analysis measured during an annual survey in 2018, 2019, and 2020, to determine trends from before and during the COVID-19 pandemic. Methods Mailed surveys sent annually included measures related to various psychosocial factors. Main Findings Response rates were 29% in 2018, 25% in 2019, and 24% in 2020. Most respondents reported average or high resilience (89% 2018-2020), high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…However, we were unable to identify a significant prevalence of mortality rates due to COVID-19 to include in this analysis. We are aware that loneliness rates increased for many older adults ( Ungar et al, 2021 ). Therefore, studies such as these, that emphasize the importance of social relationships, are vital during uncertain times.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to identify a significant prevalence of mortality rates due to COVID-19 to include in this analysis. We are aware that loneliness rates increased for many older adults ( Ungar et al, 2021 ). Therefore, studies such as these, that emphasize the importance of social relationships, are vital during uncertain times.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation is associated with negative mental and physical health outcomes in later life ( Novotney, 2019 ; Shankar et al, 2011 ). Conversely, social connection during the pandemic has been associated with lower stress and pandemic-related worries for older adults ( Nitschke et al, 2021 ; Ungar et al, 2022 ). Thus, isolation as a risk, and connection as a resilience factor have been established in recent COVID-19 literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them reported a substantial decline in at least one measure of well-being or mental health (most often loneliness and depressive symptoms) with the onset of the pandemic (Barcellos et al, 2021; Ejiri et al, 2021; Krendl & Perry, 2021; Raina et al, 2021; Stolz et al, 2021; van der Velpen et al., 2022). But some studies reported an increase in life satisfaction (Wettstein et al, 2022) and social network size (Ungar et al, 2022), or no change in loneliness (Kivi et al, 2021) and mental health (van Tilburg et al, 2020). A longitudinal study by Hansen and colleagues (2021) found that well-being among adults over 65 years in Norway was stable between January and June 2020 but broadly and substantially declined in December 2020.…”
Section: Influence Of the Pandemic On The Well-being Of Older Adultsmentioning
confidence: 99%